Nonlinear Forced Vibration Analysis of Two-Directional Functionally Graded Truncated Conical Shells - Irdayanti binti Mat Nashir (Tanjung Malim, 2024)
Nonlinear Forced Vibration Analysis of Two-Directional Functionally Graded Truncated Conical Shells by Irdayanti binti Mat Nashir